Catalytically active nitrogen-doped porous carbon derived from biowastes for organics removal via peroxymonosulfate activation - Oh, W.-D. (Elsevier B.V., 2019)
In this study, N-doped porous carbons (Nâdoped PCs) were prepared from various biowastes by thermal annealing method under inert atmosphere and compared. Due to the differences in the textural characteristics and w/w inorganic content, the choice of biowaste influenced the intrinsic (extent of N doping, graphitic N) and extrinsic (specific surface area) properties of the resultant N-doped PC. The Nâdoped PCs were employed to activate peroxymonosulfate (PMS) for bisphenol A (BPA) removal. It was found that the Nâdoped PCs prepared from spent coffee ground (PCâSC) and saw dust, with higher at. graphitic N (44â46 at.) and specific surface area (>400 m2 gâ1), performed significantly better (apparent rate constant, kapp = 0.072â0.087 minâ1) than those prepared from banana peel, orange peel and dried leaves (kapp < 0.046 minâ1). The PCâSC was selected to investigate the effects of catalyst loading and PMS dosage on BPA degradation, and the results indicated that increasing the catalyst loading is 1.5 times more beneficial than increasing the PMS dosage. The reactive oxygen species (ROS) was studied using chemical scavengers and electron paramagnetic resonance spectrometer which indicated that the 1O2 (induced from the interaction between the PCâSC and PMS) was the dominant ROS in the PCâSC/PMS system. The BPA degradation intermediates were also identified using the LC/MS/MS system and the possible BPA degradation pathways are proposed. This study conspicuously shows that biowastes can be used as a sustainable resource to produce PC for application in environmental redox catalysis. However, the right selection of biowaste is crucial to produce high-performance PC for PMS activation. Â© 2019 Elsevier B.V.